John of Damascus: More than a Compiler - Ables, Scott (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2023., 2023)
John of Damascus, the eighth century theologian of the newly re-established Jerusalem Patriarchate, remains understudied because many consider him no more than a compiler of tradition, saying nothing original. We challenge this misconception by exploring ways in which John made his sources his own, his reception history, his biography, his philosophic appropriation and unique contribution, how he presented his theology in locally significant ways, his influence on subsequent generations, and all his varied theological output in both its historical context and as received in Byzantine tradition.